Flowering seasonality and airborne pollen recent trends in Sierra de las Nieves, the southernmost National Park in continental Spain - De Gálvez-Montañez, Enrique; Trigo-Pérez, María del Mar; Recio-Criado, María Marta; Picornell Rodríguez, Antonio (Elsevier, 2024)
Sierra de las Nieves is the southernmost National Park in continental Spain and, in a global warming scenario, it is important to determine the impacts of climatic variations on the vegetation, with special relevance to their reproductive cycles. The flowering seasonality and intensity of the dominant anemophilous species usually reflect the response of the vegetation to climate variations, which can be monitored through the atmospheric pollen concentrations. In this study, airborne pollen was analysed for 6 years (2018-2023). A pollen calendar was elaborated to show the flowering seasonality and intensity of the dominant anemophilous taxa. Spring was the season with the highest airborne pollen diversity and intensity, Quercus being the pollen type with the highest concentrations. We observed that weather conditions influenced the presence of airborne pollen. Precipitation and relative humidity reduce pollen concentrations, while temperature rises increase them during the pre-peak period and reduce them during the post-peak. Wind dynamics play different roles depending on the pollen type considered given the heterogeneous distribution of the pollen emission sources. Significant advances were detected in the start date of the main pollen season of Quercus and Olea, as well as in the peak date of Quercus. On the contrary, other taxa such as Pinus or Poaceae did not show any trend. This brings to the fore that the responses to climatic variations may differ from one taxon to another, a continuous study in natural areas being required for detecting possible changes in the observed trends.
https://openpolicyfinder.jisc.ac.uk/id/publication/10459
Keywords: Polen; Palinología; Microbiología del aire; Airborne pollen; Climate change; Trends; Pollen calendar; National Park; Aerobiology